Social assistance and assistentialism in Brazil: Challenges to overcome the legacy of benevolence – an integrative review (2012-2022) (Research, Society and Development, 2025)
The objective of this study is to identify, through an integrative literature review, the challenges faced by Brazil’s public Social Assistance policy in consolidating itself as a promoter of autonomy and social development. Nine articles published between 2012 and 2022 were analyzed from the SciELO and CAPES Journals databases, using the descriptors “social assistance,” “assistentialism,” and “social rights.” It was found that, in accordance with the Brazilian socio-historical context, although Social Assistance plays a crucial role in promoting social rights, it remains biased toward assistentialism and philanthropy. The need to deepen the discussion about this context is evident. Further research is suggested to explore how this public policy is perceived by the social actors involved.